ETHNIC LANGUAGE USE AND ETHNIC IDENTITY OF DIFFERENT ETHNIC GROUPS - NURZATUL SHAZREENA, ZAINOL ABIDIN (Universiti Malaysia Sarawak (UNIMAS), 2018)
This study aims to examine the use of ethnic languages and the relationship to the ethnic identity of selected ethnic groups. The objectives of this study are; (1) to describe the ethnic language use of selected ethnic groups, (2) to identify the strength of ethnic identity (measured by Multigroup Ethnic Identity Measure) and (3) to examine the relationship between ethnic language use and ethnic identity of selected ethnic groups. The language use study across six domains involved 100 participants in Universiti Malaysia Sarawak, including participants from different ethnic groups like malay, Chinese, Indian, Iban and others. The result shows that the most used language across the six domains is standard Malay (570 reports), followed by Malay dialect (426 reports) and English (398 reports). This study also found that the four main ethnic groups reflects positive ethnic identity and behaviour. However, the study also found that there is no significant overall correlation between ethnic language use and ethnic identity strength.